Շնորհի հոգեբանական մեկնաբանությունը փոխհարաբերությունների համակարգում - Խաչատրյան Աննա; Հակոբյան Նաիրա (Բանբեր Երևանի համալսարանի. Փիլիսոփայություն, Հոգեբանություն, 2021)
The concept of blessing is interpreted from a socio-psychological point of view, the interdisciplinary methodological foundations of the formation of the concept are considered, culturological, semiotic aspects of perception are given. The article presents the results of a longitudinal study, which also includes issues of the perception of a religious blessing during and after active hostilities in the region.